MARKETİNG 4.0: INTERNET OF THİNGS (Third Sector Social Economic Review, 2019)
Recent developments in the industry have an impact on the world as well as in the marketing sector. Nowadays, customers want to satisfy their basic needs, satisfy their desires, benefit from the product, be a part of the product, contribute to the product and interact with the product.. They share their positive or negative experiences through information technologies and state whether the product fulfills their promises. Marketing 4.0 is a new trend for designing brand-consumer relationships and designing marketing strategies. it is a new generation that changes the economic activities with digital transformation. This system consists of brand identity, brand image, brand integrity and brand interaction to fulfill the market required and to meet customer needs.In parallel with the changes in technology, it can be seen that marketing activities have turned into Marketing 4.0 with new applications to satisfy consumers. Marketing now circulates around internet customers and reinforces their interaction with products. Firms take account of the feedback from users and make more efforts to satisfy them.  In this study, the aim of this study is to explain the concepts of Marketing 4.0 and Internet of Things by examining the existing literature on the relationship between them, and to create a conceptual framework and basic knowledge accumulation on the subject and contribute to the literature.
Keywords: Marketing Phases; Marketing 4.0; Digital Marketing; CustomerInteraction; Internet of things